Initial performance of three indigenous species used in an enrichment planting of hill dipterocarp forest. - Awang, Kamis; Sawal, Peter (Universiti Pertanian Malaysia, 1987)
This paper present the results of a study to examine the feasibility of using Scaphium sp., Shorea acuminata and Shorea bracteolata in an enrichment planting in relation to block, topographic and silvicultural variations. The silvicultural treatments included no treatment, fertiliser plus weeding every 6 months and weeding only every 6 months. Scaphium sp. was found to adapt well to the site, as reflected by its low mortality (10%). In contrast, S. bracteolata was physiologically intolerant of the site as reflected by a higher mortality (44%) just after 1.5 years of establishment. The performance of S. acuminata was intermediate. In terms of height growth rate (CAI), S. bracteolata was found to grow faster than other two species. Lower slope was found to promote higher CAI in all species except S. bracteolata which showed little variation in growth. The difference in CAI values could be attributed to the higher accumulation of soil nutrients downslope due to leaching and surface wash. Block II which contained lower values of most soil parameters was also found to produce poorest CAI for all species. Weeding and fertiliser plus weeding generally promoted better survival and growth. The silvicultural implications of this study are discussed.